A companion to contemporary drawing - Chorpening, Kelly; Fortnum, Rebecca (John Wiley & Sons, Inc., 2021)
"With their deviant movements, carefully defined features, and exquisitely detailed faces, the serial drawings of Kenyatta A.C. Hinkle, Titus Kaphar, and Whitfield Lovell offer refreshing approaches to visual indexes of Black bodies. For some artists, the act of drawing is only a preliminary step toward a final artwork yet to be realized. However, these artists create drawings as complete manifestations of transient forms-humans in various stages of life and death. Each presents the beauty of Blackness, not to promote its consumerism, but to provide a space for meditation on the invisibility, misrecognition, and complexity of Black people"--